2022-RA-1404-ESGO The impact of COVID19 on the diagnostic and treatment pathways for patients with endometrial cancer in Northern Ireland. (20th October 2022) - McMullan, Josh Courtney; Leitch, Emily; Wilson, Susan; Rannaghan, Lisa; Alwahaibi, Fatma; Dobbs, Stephen
Abstract : Introduction/Background: COVID-19 has significantly impacted all areas of medicine including access to primary care. The majority of women with endometrial cancer present in early stages and have promising survival outcomes. The concern is that COVID-19 has caused potential delays in diagnosis leading to patients requiring more extensive surgical management and affecting disease outcomes. Methodology: All patients diagnosed with endometrial cancer in 2019 (pre COVID-19), 2020 (during peak of COVID-19) and 2021 (during COVID-19 recovery) were included. Patients with myometrial sarcoma, other myometrial tumours and endometrial cancer recurrences were excluded. Data was collected electronically including histology, FIGO stage at diagnosis, symptom duration, parity, BMI, surgical location (regional cancer centre vs cancer unit), surgical approach and type, complications, adjuvant treatment and survival status. Statistical analysis was then performed. Results: 639 were patients identified in total (194 in 2019, 216 in 2020 and 229 in 2021). Provisional data appears to show that during COVID-19 patients present with higher FIGO stage, undergo more open surgical procedures and more extensive surgery to manage their endometrial malignancy. Conclusion: COVID-19 appears to have impacted the diagnostic and treatment pathways of women with endometrial cancer in NI. This could be due to the postponement of laparoscopic surgery following the potential risk of aerosol generation and potential delays in diagnosis due to difficult access to primary care.